Facilitated Forest Restoration Using Pioneer Seed Dispersers in Madagascar: The Example of Microcebus spp. - Jörg U. Ganzhorn; Jean-Basile Andriambeloson; Sylvia Atsalis; Lis M. Behrendt; Marina B. Blanco; An Bollen; Stéphanie M. Carrière; Lounès Chikhi; Melanie Dammhahn; Giuseppe Donati; Timothy M. Eppley; Refaly Ernest; et al. (Land)
The concept of “facilitated restoration” aims at native biodiversity reinstatement with the help of animal seed dispersers attracted by fruiting trees. Yet, large-crowned trees will have to develop in the early stages of restoration; therefore, seed dispersal provided by small generalist mammals and birds that use rapidly growing herbs, shrubs, and small trees at early stages of forest succession would accelerate biodiversity restoration. Due to the elusive lifestyle of these small animals, it is unclear what species can contribute to the early stages of this process. Using the primate genus Microcebus (adult body mass about 60 g) as an example, we illustrate that these small generalists are possible seed dispersers in the early stages of forest restoration, not yet used by larger frugivores. We show that Microcebus spp. dispersed more seeds from herbs, shrubs, and small trees than large frugivorous primate species. These plants tend to have smaller seeds than large tree species and are often pioneer species not considered in forest restoration projects. Facilitating the colonization of restoration plots by generalist small seed dispersers that use shrubby habitats may improve plant diversity by adding a more natural sequence of successional stages towards mature forests in Madagascar and elsewhere in the tropics.